Let f(x) = 7x - 2, g(x) = -x + 4, and h(x) = -4x + 1.
Perform the indicated operation.

1. f(x) + g(x)
2. f(x) + h(x)
3. h(x) + g(x)
4. f(x) - g(x)
5. h(x) - f(x)
6. g(x) - h(x)

Respuesta :

Answer:

Explanation:

1.
f(x) + g(x)
= (7x - 2) + (-x + 4)
= 7x - 2 - x + 4
= 6x + 2

2.
f(x) + h(x)
= (7x - 2) + (-4x + 1)
= 7x - 2 - 4x + 1
= 3x - 1

3.
h(x) + g(x)
= (-4x + 1) + (-x + 4)
= -4x + 1 - x + 4
= -5x + 5

4.
f(x) - g(x)
= (7x - 2) - (-x + 4)
= 7x - 2 + x - 4
= 8x - 6

5.
h(x) - f(x)
= (-4x + 1) - (7x - 2)
= -4x + 1 - 7x + 2
= -11x + 3

6.
g(x) - h(x)
= (-x + 4) - (-4x + 1)
= -x + 4 + 4x - 1
= 3x + 3
ACCESS MORE